A new species of the Spinomantis bertini species complex (Anura: Mantellidae) from Pic d’Ivohibe Special Reserve (Madagascar) - Sabino-Pinto, Joana; Rakotoarison, Andolalao; Bletz, Molly C.; Edmonds, Devin; Glaw, Frank; Vences, Miguel (Zootaxa, 2019)
We describe a new frog species of the Spinomantis bertini species complex based on congruent genetic evidence from mitochondrial and nuclear DNA sequences as well as minor morphological differences. A molecular phylogeny derived from the mitochondrial 16S rRNA gene revealed that Spinomantis mirus sp. nov. is sister to a clade containing the other two described species of the species complex, S. bertini and S. beckei, but strongly differentiated from these two species by 8.1–9.8% pairwise distances in this gene. DNA sequences from two nuclear genes revealed that S. mirus sp. nov. shares no alleles with these two species. Phenotypically, S. mirus sp. nov. differs from the other species of the complex by its larger size and some aspects of its coloration, including clear mottling on the flanks, tri-color banding on the legs, and distinct brown dots on the dorsum. The new species is so far only known from Pic d’Ivohibe Special Reserve. Its distribution thus appears to not overlap with those of the other two species, which as far as known are restricted to the Andohahela Massif in the extreme South-East of Madagascar, at a distance of about 250 km from Ivohibe.